Pensionär – aldrig i livet - De äldre i ordböckerna - Nikula, Kristina (Nordiske Studier i Leksikografi, 2007)
Today elderly people in many ways radically differ from those of former generations. One consequence of this is that terms like pensioner (Sw. pensionär) with their connotations are often not felt to be adequate any more. The same concerns the stereotype of old people as generally poor, ill and disabled. The lexicographic examples in the entries of Swedish monolingual dictionaries to an astonishingly great extent repeat this stereotype. In this paper the future of existing terms denoting old people and the introduction of new words are discussed. Further the function of lexicographic examples is discussed and the question is raised, whether the one-sided description of the elderly can be defended ethically.